Identification of two novel isoforms of mouse NUR77 lacking N‐terminal domains. Issue 2 (23rd January 2017) - Rehman, Sayeed ur; Sarwar, Tarique; Husain, Mohammed Amir; Ishqi, Hassan Mubarak; Tabish, Mohammad
Abstract: Nur77 is a member of nuclear receptor superfamily that acts as a transcription factor and regulates expression of multiple genes. Subcellular localization of Nur77 protein plays an important role in the survival and cell death. In this study, we have predicted and confirmed alternatively spliced two new transcripts of Nur77 gene in mouse. The newly identified transcripts have their alternatively spliced first exon located upstream of published 5′‐UTR of the gene. Transcription factor binding sites in the possible promoter regions of these transcripts were also analyzed. Expression of novel transcript variants was found to be significantly lower than the already published transcript. New transcript variants encode for NUR77 protein isoforms which are significantly smaller in size due to lack of transactivation domain and a part of DNA binding domain. Western blot analysis using NUR77 specific antibody confirmed the existence of these smaller variants in mouse. Localization of these new isoforms was predicted to be majorly outside the nucleus. In silico analysis of the conceptually translated proteins was performed using different bioinformatics tools. The results obtained in this study offer further insight into novel area of research on extensively studied Nur77. © 2017 IUBMB Life, 69(2):106–114, 2017